Effects of soil type on the growth of polytrichum commune - Ong, Ghim Hock; Boey, Mervin, Jia Ye; Cheng, Wan Hee (INTI International University, 2020)
Mosses, classified as bryophytes, are of economic importance in the horticulture industry where they are used for decoration and gifts. Polytrichum commune (common haircap moss) is a popular moss species used in TerraLiving’s terrariums. However, moss growth is slow, taking up to 12 months for complete growth which limits its economic value. Moss is conventionally grown on peat soil but its prolonged use under the slow moss growth is uneconomical. Therefore, synthetic soil has been proposed as an alternative growth media. Hence, the aims of this study are to investigate the physicochemical characteristics of both peat and synthetic soils which affect the growth of common haircap moss (in terms of increase in horizontal length and number of shoots). Soil pH and cation exchange capacity (CEC) to study the rationale behind. Polytrichum commune was grown in both peat and synthetic soils over a course of 6 weeks (after an acclimatization period of 2 weeks) to determine their rate of growth in different soil types, measured in terms of horizontal length increment (in mm) and number of new shoots. It was observed that the moss grown in peat soil exhibited greater horizontal growth (9.280 ± 2.756 mm) than synthetic soil. This is heavily linked to the significantly lower pH and higher CEC of peat soil. The number of shoots formed was similar in both peat and synthetic soil (8.267 ± 1.535 and 7.8 ± 0.803 respectively), possibly due to similar levels of phytohormone production. In conclusion, peat soil is a better media for the growth and cultivation of P. commune.